Building Capacity for Injury Prevention: A Process Evaluation of a Replication of the Cardiff Violence Prevention Program in the Southeastern United States - Kollar, Laura M. Mercer (Inj Prev, 2019)
OBJECTIVES: Violence is a major public health problem in the United States. In 2016, more than 1.6 million assault-related injuries were treated in U.S. emergency departments. Unfortunately, information about the magnitude and patterns of violent incidents is often incomplete and underreported to law enforcement (LE). In an effort to identify more complete information on violence for the development of prevention programs, a cross-sectoral Cardiff Violence Prevention Programme (Cardiff Model) partnership was established at a large, urban emergency department (ED) with a level I trauma designation and local metropolitan LE agency in the Atlanta, Georgia metropolitan area. The Cardiff Model is a promising violence prevention approach that promotes combining injury data from hospitals and LE. The objective was to describe the Cardiff Model implementation and collaboration between hospital and law enforcement partners. METHODS: The Cardiff Model was replicated in the United States. A process evaluation was conducted by reviewing project materials, nurse surveys and interviews, and ED-LE records. RESULTS: Cardiff Model replication centered around four activities: (1) collaboration between the hospital and LE to form a community safety partnership locally called the United States Injury Prevention Partnership; (2) building hospital capacity for data collection; (3) data aggregation and analysis; and (4) developing and implementing violence prevention interventions based on the data. CONCLUSIONS: The Cardiff Model can be implemented in the U.S. for sustainable violent injury data surveillance and sharing. Key components include building a strong ED-LE partnership, communicating with each other and hospital staff, engaging in capacity building, and sustainability planning.